Japanese-Canadian Internally Displaced Persons: Labour Relations and Ethno-Religious Identity in Southern Alberta, 1942–1953 - Fujiwara, Aya (Labour / Le Travail, 2012)
This article examines the resettlement of Japanese-Canadian internally displaced persons (idps), who were relocated from the West Coast of British Columbia to sugar beet communities in southern Alberta between 1942 and 1953. It argues that the idps, assisted both by pre-World War II Japanese residents in southern Alberta and by the federal government, contributed to the rising awareness of ethnic rights. For this purpose, my study adds two new angles to the study of human rights and Japanese Canadians. First, while ethnic activism for human rights has often been examined in an urban context, it was the negotiations in the local sphere between the Alberta Sugar Beet Growers’ Association and Japanese idps that played a significant role in promoting human rights. Second, this study applies both local and transnational contexts to the question of Japanese-Canadian idps, which has hitherto been studied only in terms of state violence against an ethnic minority. The Japanese idps retained Pure Land Buddhism as a symbol of their loyalty to Japan, and the religion strengthened its influence in southern Alberta as a focal point of their identity.